2022
DOI: 10.1186/s12885-022-09745-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an interactive acceptance and commitment therapy (ACT) workshop delivered to trained therapists working with cancer patients in the United Kingdom: a mixed methods approach

Abstract: Background SURECAN (SUrvivors’ Rehabilitation Evaluation after CANcer) is a multi-phase study developing and evaluating an Acceptance and Commitment Therapy (ACT) intervention integrated with exercise and work when highly valued (thus we called the intervention ACT+), for people who have completed treatment for cancer but who have low quality of life. We developed a training programme for therapists working in different psychological services to be delivered over 2–3 days. Our aim was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…These negative attitudes, in turn, exacerbate their current helplessness and weaken their motivation to use social and psychological resources to help them cope with the difficulties they face. 24 Acceptance-centred counselling modalities, such as acceptance and commitment therapy (ACT), 59 play important roles in helping individuals adjust to MHD and the accompanying life changes, improve their negative attitudes, and increase their self-identity.…”
Section: Discussionmentioning
confidence: 99%
“…These negative attitudes, in turn, exacerbate their current helplessness and weaken their motivation to use social and psychological resources to help them cope with the difficulties they face. 24 Acceptance-centred counselling modalities, such as acceptance and commitment therapy (ACT), 59 play important roles in helping individuals adjust to MHD and the accompanying life changes, improve their negative attitudes, and increase their self-identity.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large number of studies identified, we restricted the scope to UK studies from 2010 onwards. Restricting papers to the UK ensured that the findings better related to the NHS context, where the main SURECAN trial was conducted [ 6 ]. Cancer survival continued to improve across the UK (and other high income countries) between 1995 and 2014, although between country differences have persisted [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is clear that better ways of conceptualising racially minoritised health care are needed. We began this meta-ethnography with an interest in the social and cultural influences on cancer-related psychological interventions to inform our work on developing and evaluating an intervention for people living with and beyond cancer experiencing psychological distress [ 6 ]. The process of conducting this meta-ethnographic review led to the elaboration of the concept of ‘animated by (frequently hidden) affective relationality’ in the final synthesis, tying all the themes together.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapists attend an ACT+ training workshop delivered over two to three days and receive regular supervision during the trial from an experienced cognitive behavioural therapist with extensive training in ACT. We have reported in more depth on the development and evaluation of the training (Moschopoulou et al, 2022). Additional information about the intervention will be available in the protocol for the main quantitative trial looking at the effectiveness and cost-effectiveness of the ACT+ intervention, to be published in the public domain…”
mentioning
confidence: 99%